2016
DOI: 10.4034/rbcs.2016.20.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Análise Das Funções Do Sistema Estomatognático Em Idosos Usuários De Prótese Dentária

Abstract: RESUMOObjetivo: Avaliar as funções do sistema estomatognático em idosos usuários de prótese dentária. Material e Métodos: Realizou-se avaliação fonoaudiológica constituída por uma anamnese e uma avaliação clínica composta por duas etapas. Na primeira etapa, foram observadas as características corporais e faciais gerais. Na segunda etapa, realizouse avaliação das estruturas orofaciais e das funções orais por meio da observação e apalpação. Foram incluídos indivíduos com mais de 60 anos, usuários de prótese dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
0
5
0
9
Order By: Relevance
“…This datum corroborates the literature findings, confirming that after prosthetic rehabilitation there is greater masticatory performance (14)(15)(16)25) . However, the study by Ayres et al (26) found that prosthetic rehabilitation causes changes in the stomatognathic system, with an impact on mastication, because the individuals who undergo this process have reduced facial muscle tonus, when compared to individuals who do not use dental prosthesis. Only 12% of the GI did not use any type of dental prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This datum corroborates the literature findings, confirming that after prosthetic rehabilitation there is greater masticatory performance (14)(15)(16)25) . However, the study by Ayres et al (26) found that prosthetic rehabilitation causes changes in the stomatognathic system, with an impact on mastication, because the individuals who undergo this process have reduced facial muscle tonus, when compared to individuals who do not use dental prosthesis. Only 12% of the GI did not use any type of dental prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…These deteriorations interfere in chewing properly and in the swallowing and speaking functions, which will restrict and interfere with social and family activities. The dental prosthesis aims to reestablish these aspects changed due to the edentulism and to provide better quality of life regarding feeding and, consequently, improving the elderly general health condition (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Oral health is often cited as an indicator of quality of life, since changes such as dental loss and difficulty chewing influence the life of individuals and may affect feeding 16,17 . Ayres et al 10 mention that the use of removable dental prosthesis leads to instability in chewing, causing insecurity in the user, who will consequently abstain from eating certain foods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as the individual ages, their chewing habits change. It is known that dental problems, when associated with speech problems, as well as with aging, may be harmful to health 10 . Therefore, these factors can disrupt the individual's routine, because even if the older adult's functional capability is in its normal state, chewing and swallowing affect his/her manner of eating and diet, which may be associated with anemia in these individuals.…”
Section: Introductionmentioning
confidence: 99%